Computational inference of chemokine-mediated roles for the vagus nerve in modulating intra- and inter-tissue inflammation - Shah, Ashti M.; Zamora, Ruben; Barclay, Derek; Yin, Jinling; El-Dehaibi, Fayten; Addorisio, Meghan; Tsaava, Tea; Tynan, Aisling; Tracey, Kevin; Chavan, Sangeeta S.; Vodovotz, Yoram (Frontiers in Systems Biology, 2024)
The vagus nerve innervates multiple organs, but its role in regulating cross-tissue spread of inflammation is as yet unclear. We hypothesized that the vagus nerve may regulate cross-tissue inflammation via modulation of the putatively neurally regulated chemokine IP-10/CXCL10. Rate-ofchange analysis, dynamic network analysis, and dynamic hypergraphs were used to model intra-and inter-tissue trends, respectively, in inflammatory mediators from mice that underwent either vagotomy or sham surgery. This analysis suggested that vagotomy primarily disrupts the cross-tissue attenuation of inflammatory networks involving IP-10 as well as the chemokines MIG/CXCL9 and CCL2/MCP-1 along with the cytokines IFN- and IL-6. Computational analysis also suggested that the vagusdependent rate of expression of IP-10 and MIG/CXCL9 in the spleen impacts the trajectory of chemokine expression in other tissues. Perturbation of this complex system with bacterial lipopolysaccharide (LPS) revealed a vagally regulated role for MIG in the heart. Further, LPSstimulated expression of IP-10 was inferred to be vagus-independent across all tissues examined while reducing connectivity to IL-6 and MCP-1, a hypothesis supported by Boolean network modeling. Together, these studies define novel spatiotemporal dimensions of vagus-regulated acute inflammation.